Job stress, organizational justice, empowerment and alternative employment opportunities influencing employee turnover intention in SME bank / Abdul Muhaimin Abdul Manab and Athirah Imanina Abdul Rahim - Abdul Manab, Abdul Muhaimin; Abdul Rahim, Athirah Imanina (2020)
Employee is an important asset in an organisation where they play a significant role in organisation’s success in a competitive environment. However, turnover intention among the employees has becomes a major obstacle towards the organization as it impacts the productivity of the organization. Recent study by the Institute of Labour Market Information and Analysis (ILMIA), found out the employee turnover rate in Malaysia displayed an increasing trend from 15% in 2015 to 20% in 2017. Following to the situation in SME Bank where it reported in its Annual Report 2017 where there is a decreasing trend of 4% in the number staffs in the year 2015 to 2017 and it has raised a concern to the management as the organisation loss numbers of its talents in the process. Based on the literatures obtained, job stress, organisational justice, empowerment, and alternative employment opportunities are identified to influence employees’ turnover intention at SME Bank. The result obtained from 250 respondent shows that job stress and alternative employment opportunities have positive influences on the employees’ turnover intention at SME Bank. On the other hand, distributive justice, procedural justice and empowerment have negative influences on the employees’ turnover intention. Several recommendations for the management are suggested in this study in order to reduce the turnover intention among employees of SME Bank.